Cardiorespiratory capacity of adolescents aged 12 to 16 of both sexes who swim (Research, Society and Development, 2025)
Swimming is a sport that works on several physical abilities, including cardiorespiratory capacity, which was the subject of this study. The objective of this test was to use a 12-minute test adapted for the aquatic environment to analyze whether swimmers aged 12 to 16 of both sexes are within the parameters of their age and sport in terms of their cardiorespiratory capacities. Eleven adolescents aged 12 to 16 who are swimmers in the UPF Future Athlete Project were evaluated. These individuals were invited to take the 12-minute test adapted for swimming. The distance each swimmer swam was recorded in meters and the results were analyzed using the “Cooper Physical Fitness Level” table, adapted to take into account the circumstances of the pool test. It was concluded that swimming is an extremely individual and specific sport, where even athletes from the same group presented noticeably different performances, showing that practice, consistency and dedication in training have a great influence on learning and individual performance.